강변여과에 의한 이·취미 물질 제어 특성에 관한 타당성 연구 - 맹승규; 박노석; 임재림; 김성수; 정우창 (대한상하수도학회, 2010)
This study was conducted in order to investigate bulk organic matter characteristics and behavior of geosmin and 2-methylisoborneol (2-MIB) during riverbank filtration, which are general surrogates of taste and odor in drinking water. Column studies were used to simulate bank filtration systems. Most of the aliphatic organic matter was removed effectively after soil passage, and it is believed to be polysaccharides according to LC-OCD and F-EEM analysises. Removal efficiencies of geosmin and 2-MIB within the filtration column reached above 95%. It was found that the removal of total dissolved organic matter has a correlation with that of geosmin and 2-MIB in the near of filtration surface (about 50cm).